Integrative Model of Conflict Management in Islamic Educational Institutions An Analysis of Types and Sources of Organizational Conflict - Masruroh Jazuli; Lutfatul Ummul Mahmudah Lutfatul; Zayda Nasby Muzakky Nasby; Zanuba Arifah Nur Azzakra Azzakra; Hudan Ngisa Anshori Anshori (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
Conflict is a phenomenon that is inseparable from the dynamics of organizational life, including in Islamic educational institutions that involve various interests and interactions between individuals and groups. Differences in values, perceptions, and limited resources are the main factors in the emergence of organizational conflicts. This study aims to analyze the types, sources, and interactive models of conflict management in Islamic educational institutions. The approach used is qualitative through library research by reviewing relevant literature. The results of the study show that conflict is an inseparable phenomenon from the dynamics of educational organizations. Conflicts can occur in various forms, such as intrapersonal, interpersonal, intragroup, intergroup, and organizational conflicts, with diverse sources. The application of an integrative model that prioritizes Islamic values is important to create harmony and improve the quality of the organization. Thus, proper conflict management is not only able to minimize negative impacts but also the sustainability of Islamic educational institutions